Cultural Dyphemisms in the Turkish Culture Region - İlhami Durmuş (Gazi Akademik Bakış)
Turkish steppe culture constituted a typical structure with regard to its creation and development. It emerged from steppe geography. The geography affected social, politic, economical, military and religious structure of the society substantially. The Turkish culture was shaped up under these influences. The agents of the culture appeared as a shepherd generally. Shepherding provided a basic to the animal husbandry. The shepherds headed to search the fertile grass. Shepherding obliged people to became seminomadic. Thus the life continued in a manner of searching new pastures and shuttling between plateau and winter quarters . The horse that is one of the important ingredient of the culture provided mobility and speed to the culture. In social, politic, and military life of society the horse came into prominence. The nomadic houses or the cars contributed to Turks’ life very much. These nomad houses were shelter at the nights and cold days for them. Going from the plateau to winter quarters and from pasture to another pasture was made easy thanks to these. The finding which took out from graves reflects to all features of the culture.The ruins of nomad houses and horses were arised from the graves . These support the informations which was given in the written sources. Among the findings, there were also The animal struggle scenes which reflect art concept of theseminomadism between tomb finds. This art concept named as turkish animal style. It’s tried to determine The scope of the Turkish culture by emphasizing steppe, shepherding, semi-nomadism, horse, nomad house, tomb. It is also emphasized that aforementioned notions can be used for Turkish culture. Thus, cultural dysphemisms in the turkish culture based on that idea.